A COMPREHENSIVE STUDY ON THE WORKING, USAGES, APPLICATIONS, AND IMPACT OF FIVE WORKING ORGANS (KARMENDRIYA) AND FIVE SENSE ORGANS (GYANENDRIYA) IN THE HUMAN BODY - 1. Prof. Dr. Rajender Pal , 2. Dr. Sumitra Behera (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
(The human body functions as an integrated system, where organs and sensory mechanisms interact to support physical actions, cognitive processing, and overall survival. In traditional Indian philosophy, particularly in Ayurveda and Sankhya, the five working organs (Karmendriyas) and five sense organs (Gyanendriyas) form the foundation of physiological and psychological functions. This study aims to explore their anatomy, physiological mechanisms, applications in modern medical science, and the impact of their optimal and impaired functioning on health and quality of life. By integrating modern biomedical understanding with classical knowledge, this research highlights how these organs coordinate to sustain human interaction with the environment and self-awareness.)